Functional Limit Theorem for Products of Sums of Independent and Nonidentically Distributed Random Variables - Przemysław Matuła; Iwona Stępień (Journal of Mathematics)
We study the weak convergence in the space of processes constructed from products of sums of independent but not necessarily identically distributed random variables. The presented results extend and generalize limit theorems known so far for i.i.d. sequences.